(1266) The generation of all efficient extreme points for a multiple objective linear program توليد جميع النقاط القصوى الفعالة لبرنامج خطي متعدد الأهداف - Omar, Amani (The Institute Of National Planning., 2018)
It has frequently been argued that the traditional approximation of multiple goals of the decision models by a single crition is either inappropriate or incorrect. In reality, decision situation is characterized by a series of confliction goals. And it might be an impossible task to tie all goals into a single unifying trade..off function.